Relativistic study of electromagnetic electron cyclotron instability based on trapped electrons in kappa‐Maxwellian auroral plasmas. Issue 7 (19th March 2021) - Nazeer, M.; Qureshi, M.N.S.; Shen, C.
Abstract: The presence of relativistic electrons in the Earth's magnetosphere may excite EMEC waves via resonant interaction. The understanding of EMEC waves induced by such electrons requires relativistic treatment. Therefore, we present here the investigation of EMEC waves based on relativistic trapped electrons represented by kappa‐Maxwellian distribution in auroral plasmas. The analytical expressions of real frequency and relativistic growth rate are derived. Our numerical outcomes report that relativistic approximation increases the wave growth and causes reduction in the threshold value of drift velocity of trapped electrons for instability. The wave frequency that corresponds to the maximum growth decreases as we go from nonrelativistic limit to relativistic. The maximum growth increases with the increment in plasma frequency, perpendicular thermal velocity, drift velocity of trapped electrons, and Lorentz factor γ . Moreover, the relativistic effects on maximum growth are more pronounced for smaller values of drift velocity and perpendicular thermal velocity. Abstract :